Genomic analyses inform on migration events during the peopling of Eurasia - Pagani, Luca; Eichstaedt, Christina (Nature, 2016)
Whole-genome sequencing of individuals from 125 populations provides insight into patterns of genetic diversity, natural selection and human demographic history during the peopling of Eurasia and finds evidence for genetic vestiges of an early expansion of modern humans out of Africa in Papuans.